Equal cerebral perfusion during extended aortic coarctation repair - Rüffer, André; Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Wölfle, Joachim; Jüngert, Jörg M. (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Aortic coarctation with distal aortic arch hypoplasia can be effectively addressed by coarctation resection with extended end-to-end-anastomosis (REEEA). Particularly, when unilateral cerebral perfusion (UCP) is established by clamping of left-sided supra-aortic vessels, the extent of cerebral blood flow distribution during repair remains undetermined, so far. Transfontanellar contrast-enhanced ultrasound (T-CEUS) can be utilized for real-time visualization and quantitative evaluation of cerebral blood flow. This study quantitatively evaluates cerebral perfusion during REEEA by using intraoperative T-CEUS. METHODS: In a prospective study, 9 infants with open fontanelle undergoing REEEA [median age: 13 days (range 1-34) and median weight 3.1 kg (range 2.2-4.4)] were intraoperatively examined with T-CEUS at 3 consecutive time-points: before skin incision, during UCP and after skin suture. A software-based analysis of 11 parameters was used for data evaluation. Absolute and relative blood flow in contralateral hemispheres was measured in side-by-side comparison, and referenced to baseline measurements. RESULTS: No side-depend absolute or relative cerebral perfusion differences were found during REEEA, except for an increased relative 'wash-out-rate' (P = 0.0013) in favour of the right hemisphere after surgery. Compared to ipsilateral baseline levels, 'rise time' was transiently increased in right (P = 0.0277) and 'time-to-peak' in both hemispheres (right: P = 0.0403 and left: P = 0.0286), all during UCP. CONCLUSIONS: The use of T-CEUS provided evidence for homogenous distribution of contrast agent in both hemispheres during UCP. T-CEUS can be utilized for the postprocedural evaluation of cerebral perfusion during congenital cardiac surgery. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov Unique, Identifier: NCT03215628.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Aortic coarctation; Cerebral perfusion; Extended end-to-end-anastomosis